A fighter journalist: Clovis Moura, Flama and the PCB's cultural politics (1951-1952). - Malatian, Teresa [UNESP] (FapUNIFESP (SciELO), 2019)
Clovis Moura (1925-2003) has been studied by his most known works of History and Sociology, some of them considered today as classics, as Rebellions of Senzala. However, one important dimension of his intellectual activity, as a journalist, remains obscure, even though relevant. On this article the intention is to approach the review Flama, created and directed by him in the city of Araraquara (SP), in the ambit of the Cultural Policy developed by the Brazilian Communist Party (PCB) . With ephemeral duration ( 1951- 1952), the publication de serves be featured by its content lined upwith the party, as well by the relevant intellectuals and politics nets of sociability build by its creator and director. A third aspect refers to the policy repressionthat motivated, accessed in the DEOPS - Sao Paulo files.
Um jornalista combatente: Clóvis moura, flama e a política cultural do PCB (1951-1952)
Keywords: Clovis Moura; Communist press; Flama review